WAKF BASED EDUCATION GOVERNANCE IN REALIZING ISLAMIC EDUCATION INSTITUTIONS QUALITY - Eddy Saputra; Achmad Muhajir (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
Ideally, education can be accessed by every level of society. There are still problems in the world of education, especially for people with low incomes. The potential of waqf is being promoted and developed in this country. But it is unfortunate that the financing has only been allocated only as a strengthening of state finances in the form of buying sukuk. Governance has great potential in realizing a quality Islamic Educational Institution so that it can be reached by anyone, so through this research, the researcher proposes to the Indonesian waqf agency to also participate in developing National scale Islamic education that can be accessed by anyone, given the huge potential for waqf, especially in Indonesia. Where there are several quality and large educational institutions abroad because of the independence of their institutions which are financed by waqf. This research uses descriptive qualitative method. This research was conducted in order to aim at a quality Islamic Education Institution through the empowerment of waqf. Idealnya Pendidikan dapat di akses oleh setiap lapisan masyarakat. Masih adanya problematika dalam dunia Pendidikan terlebih bagi masyarakat yang berpenghasilan rendah. Potensi wakaf sedang digalakkan dan dikembangkan di negeri ini. Tetapi sangat disayangkan pembiayaannya baru dialokasikan hanya sebagai penguatan keuangan negara dalam bentuk pembelian sukuk, tata Kelola memilki potensi besar dalam mewujudkan Lembaga Pendidikan Islam yang berkualitas sehingga dapat dijangkau oleh siapa saja, maka melalui penelitian ini, peneliti mengusulkan kepada badan wakaf Indonesia juga ikut mengembangkan Pendidikan Islam skala nasional yang dapat diakses oleh siapa pun, meningat potensi wakaf begitu besar khusunya di Indonesia. Dimana ada beberapa lembaga pendidikan di luar negeri berkualitas dan besar karena kemandirian lembaganya yang dibiayai oleh wakaf. Penelitian ini menggunakan metode kualitatif deskriptif. Penelitian ini dilakukan agar bertujuan Lembaga Pendidikan Islam yang berkualitas melalui pemberdayaan wakaf.